Biophysical modifications during El Niño phenomenon and its correlation with Talara epidemic encephalitis virus 1997-1998 - Briceño Aliaga, Mónica (2016)
El Niño occurs every 4 to 7 years; It is part of a natural event atmospheric Ocean known as El Nino Southern Oscillation (ENSO). Under normal conditions, on the west side of the Pacific Ocean there is a sea temperature of 29 ° C and a system of low atmospheric pressure in Darwin, Australia, while on the east side there is a high pressure system in Papeete-Tahiti, and level of the coasts of Peru and Ecuador sea temperature is 19 to 23 ° C. The cold waters of the eastern Pacific condition in the atmosphere high pressure zones and warm waters, areas of low pressure. The pressure difference causes the trade winds traveling from east to west, dragging surface waters and producing an upwelling phenomenon, whereby, the colder waters of the sea bottom out at the surface. The deep waters are rich in salts and micronutrients for the formation of phytoplankton base of the food chain in fish.